Approaching the Grammatical Count/Mass Distinction From a Multimodal Perspective. Issue 3 (15th September 2015) - Brown, Derek J.
Abstract : The way in which the count/mass distinction (CMD) is realized in English can cause serious problems for learners. Cognitive theories of language propose that it is based on the speaker's conceptualization of the world. It has also been argued that this conceptualization is socially constructed, as social semiotic resources influence what a speaker may regard as salient when distinguishing between count and mass nouns. Examples of this can be seen in the way different cultures realize the concept of countability in their languages. If the grammatical CMD is a realization of socially constructed conceptualization, then it is possible that by understanding the basis for the distinction in that particular language learners would be better able to apply those principles and construct meaning in that language. This article explores how, using a multimodal approach, students can be empowered as meaning makers by instructing them in the ideas of boundedness, homogeneity/heterogeneity, perceptual conspicuousness, and function, as they interact to understand the grammatical CMD in both their own language and in the target language, English.